Spatial and temporal changes in the volatile profile of alphonso mango upon exogenous ethylene treatment - Chidley, Hemangi G.; Kulkarni, Ram S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Food Chemistry, 2013)
Alphonso is a highly favoured and exported mango cultivar among the vast mango germplasm of India. Being a climacteric fruit, ethylene plays an important role in ripening of mango. For deeper understanding of effect of pre-climacteric ethylene treatment on volatile profiles of Alphonso mango, 26 volatiles were tracked through six ripening stages of pulp and skin of ethylene-treated and control Alphonso fruits. The study revealed accelerated ripening in terms of early appearance of ripening-specific compounds, lactones and mesifuran, upon ethylene treatment. While the level of lactones remained unaffected, the mesifuran level vastly increased upon ethylene treatment. Skin showed high terpene content while pulp had higher amount of lactones compared to skin. This work points towards involvement of ethylene as a natural hormone in the biosynthesis of lactones and furanones in naturally ripened fruits; whereas, an increase in the terpene level during ripening appears to be independent of ethylene. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Ethylene; Flavour; Mango; Pre-climacteric; Ripening; Volatiles